SMUT FUNGI PARASITIC ON CEREALS IN KASHKADARYA VILOYATE (ORDER USTILAGINALES) - Eshonkulov Najim; Eshonkulova Charos Najmiddinovna (Web of Journals Publishing, 2025)
Smut fungi parasitizing cereals in the Kashkadar region (Order Ustilaginales). The article studied the distribution of smut fungi on cereals in the Kashkadar region.
Keywords: Ustilaga, corn, sorghum, rye, host plants.